Orthodontic root resorption associated with surgical adjunctive procedures for accelerating tooth movement: a systematic review of randomised controlled trials - Shukla Khilan; Currell Scott Derek; Knight Beau; Baghaie Hooman; Nikolarakos Dimitrios; Dreyer Craig (Sciendo, 2022)
The present systematic review assesses the literature which identifies an association between surgical adjunctive procedures for accelerating tooth movement (SAPATM) during orthodontic therapy and orthodontically induced external root resorption (OIERR). By determining the level of association, the results may provide clinical evidence for minimising the deleterious effects of orthodontic tooth movement.